PsycEXTRA Dataset 2011
DOI: 10.1037/e519702015-087
|View full text |Cite
|
Sign up to set email alerts
|

The Cheater's High: The Unexpected Affective Benefits of Unethical Behavior

Abstract: Many theories of moral behavior assume that unethical behavior triggers negative affect. In this article, we challenge this assumption and demonstrate that unethical behavior can trigger positive affect, which we term a "cheater's high. " Across 6 studies, we find that even though individuals predict they will feel guilty and have increased levels of negative affect after engaging in unethical behavior (Studies 1a and 1b), individuals who cheat on different problem-solving tasks consistently experience more po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
38
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 0 publications
2
38
0
Order By: Relevance
“…This increased self-awareness makes them more likely to evaluate whether their behavior meets personal ethical standards (Rockmann & Northcraft, 2008), which should curtail opportunistic behavior motivated purely by self-interest. The prospect of violating one's ethical standards triggers an anticipation of negative affect (Ruedy, Moore, Gino, & Schweitzer, 2013) and lay theories about gaze aversion are consistent with this notion. Although gaze aversion is not a reliable cue to deception (DePaulo et al, 2003), the faulty lay perception that it is (Rotenberg & Sullivan, 2003;Vrij & Granhag, 2007) may reflect expectations of a nonverbal reaction to shame (Keltner & Harker, 1998) triggered by telling a lie.…”
Section: Introductionsupporting
confidence: 50%
“…This increased self-awareness makes them more likely to evaluate whether their behavior meets personal ethical standards (Rockmann & Northcraft, 2008), which should curtail opportunistic behavior motivated purely by self-interest. The prospect of violating one's ethical standards triggers an anticipation of negative affect (Ruedy, Moore, Gino, & Schweitzer, 2013) and lay theories about gaze aversion are consistent with this notion. Although gaze aversion is not a reliable cue to deception (DePaulo et al, 2003), the faulty lay perception that it is (Rotenberg & Sullivan, 2003;Vrij & Granhag, 2007) may reflect expectations of a nonverbal reaction to shame (Keltner & Harker, 1998) triggered by telling a lie.…”
Section: Introductionsupporting
confidence: 50%
“…Put simply, our moral evaluations and decisions are not only guided by conscious rational thought processes but also by quick and affect-laden processes (e.g. Ruedy, Moore, & Gino, 2013).…”
mentioning
confidence: 99%
“…Wood and colleagues (1997) stated that the positive emotional response associated with deviant behavior would be a psychological reward that reinforced the behavior. In a series of six studies, Ruedy et al (2013) found that contrary to many predictions, rather than feeling negative emotions such as remorse after amoral behavior, individuals tended to report feelings of positive emotions more frequently. Ruedy and colleagues (2013) termed these positive emotions a cheater's high.…”
Section: Direct Effects Of Theory Constructsmentioning
confidence: 99%
“…This thrill-seeking is a drive in all of us to varying degrees and can be a reinforcing reward on its own. Several studies have found a connection between crime or immoral behavior and positive feelings (Brezina & Aragones, 2004;Romer & Hennessy, 2007;Ruedy et al, 2013;Schaefer, 2016).…”
Section: Theoretical Constructsmentioning
confidence: 99%
See 1 more Smart Citation